Women of color and the reproductive rights movement - Nelson, Jennifer (New York University Press, 2003)
While most people believe that the movement to secure voluntary reproductive control for women centered solely on abortion rights, for many women abortion was not the only, or even primary, focus.Jennifer Nelson tells the story of the feminist struggle for legal abortion and reproductive rights in the 1960s, 1970s, and early 1980s through the particular contributions of women of color. She explores the relationship between second-wave feminists, who were concerned with a woman's right to choose, Black and Puerto Rican Nationalists, who were concerned that Black and Puerto Rican women have as many children as possible "for the revolution," and women of color themselves, who negotiated between them. Contrary to popular belief, Nelson shows that women of color were able to successfully remake the mainstream women's liberation and abortion rights movements by appropriating select aspects of Black Nationalist politics--including addressing sterilization abuse, access to affordable childcare and healthcare, and ways to raise children out of poverty--for feminist discourse.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; afro-féminisme; amériques; approches et analyses; discipline; femmes* de couleur; histoire; justice reproductive; militance; périodes historiques; régions géographiques; sciences humaines; sociologie; sofia; thématiques; états-unis

Le projet féministe à l’aube du XXIe siècle : un projet de libération et de solidarité qui fait toujours sens - Descarries, Francine (Cahiers de recherche sociologique, 1998)
En situant les rapports de genre au cœur de leur élaboration conceptuelle et en inscrivant leur transformation comme un enjeu stratégique, les études féministes se sont progressivement imposées dans l'univers des sciences humaines comme une approche critique et comme une problématique du changement. Après une revue des trois grands courants de pensée qui se sont développés au sein et en marge du mouvement féministe au cours des dernières décennies, l'auteure se demande si la pensée féministe, ou plutôt les différents courants de la pensée féministe actuelle sont encore engagés dans ces mêmes fins. Sont-elles encore capables de contribuer au renouvellement des savoirs, de proposer un projet de société original, et d'imaginer les termes d'un nouveau contrat entre les genres ? Sont-elles capables de nourrir une lutte féministe unie, une politique de coalition ouverte à la diversité et à la différence, mais qui ne perd rien de sa cohésion et de sa force de ralliement ? Ces questions servent de pistes thématiques pour la discussion de l'auteur.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; approches et analyses; discipline; fem1000; féminisme matérialiste; histoire et politique; justice sociale; militance; mouvements des femmes*; mouvements féministes; occident; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; sciences humaines; sociologie; thématiques